PENINGKATAN KETERAMPILAN PROSES SAINS DENGAN MENERAPKAN PENDEKATAN STEAM - Hariandi, Joe; Sitompul, Stepanus Sahala; Habellia, Ray Cinthya (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to determine the increase in students science process skills after the STEAM approach is applied and to determine the effectiveness of the STEAM approach on students science process skills in the subject of temperature and expansion at SMP Negeri 21 Pontianak. The research design uses the One Group pretest-posttest design and the research instrument uses science process skills test questions. Data collection techniques using measurement techniques, observation, interviews, and documentation. Data analysis was used to determine science process skills before and after being given treatment and to find out students science process skills based on their categories and indicators. Based on the data analysis carried out in this study, there was an increase in students science process skills in the subject of temperature and expansion which were taught using the STEAM approach. Judging from the results of the average score of science process skills before being applied at 31.80 and after being applied at 74.11. The increase in KPS can also be seen from the N-GAIN value of 0.617 so that it is in the medium category. Then for the effectiveness of the STEAM approach to improving science process skills using the Effect Size, a value of 3.89 is obtained so that it is included in the high category